Pennsylvanian and Cisuralian palynofloras from the Los Sauces area, La Rioja Province, Argentina: Chronological and paleoecological significance - Di Pasquo Lartigue, Maria (2010)
Three outcrops of the Libertad and Sauces Formations from the Los Sauces area La Rioja Province, western Argentina, yielded the nine palynoassemblages studied here. Two assemblage zones are defined on the basis of the stratigraphic distribution and ranges of seventy five species of palynomorphs (42 species of spores, 32 pollen taxa and one fungus). Only thirteen species are common to both assemblages and ten species are first records for the Paganzo Basin. Assemblage 1 from the Libertad Formation is dominated by trilete spores of Cristatisporites (lycophyte) and Punctatisporites (pteridophyte). Monosaccate pollen (Coniferales/Cordaitales) is frequently present. Pteridosperms, mostly represented by Cyclogranisporites, are especially abundant in one level together with scarce striate bisaccate pollen grains. Assemblage 2 of the Sauces Formation is dominated by trilete spores related to the Pteridophyta (e.g., Horriditriletes, Converrucosisporites, Granulatisporites) and Sphenophyta. Monosaccate (Cordaitales/Coniferales) and taeniate and non-taeniate bisaccate pollen grains (Pteridospermales/Coniferales), are equally subordinated. Monosulcate pollen (Cycadophyta) and fungi (Portalites gondwanensis) are rare. Assemblage 1 is mainly Moscovian; assemblage 2 Asselian-Sakmarian. This interpretation is based on correlation of assemblage 1 to the DMb (Mid Pennsylvanian) and assemblage 2 to the FS (Early Cisuralian) Biozones of the Paganzo Basin (Argentina). The taxonomic composition of the Ahrensisporites cristatus-Crucisaccites monoletus (Mid-Late Pennsylvanian) and the Protohaploxypinus goraiensis Subzone (Asselian-Sakmarian) of the Vittatina costabilis (Early Cisuralian) Biozones of the Paraná Basin (Brazil) support this correlation. The continental freshwater depositional setting of this part of the Paganzo Basin is supported by the dominance of terrestrial palynomorphs and phytoclasts, the presence of coal and carbonaceous shales, and the occurrence of plant megafossils and plant debris in the sediments. The floristic changes between assemblages 1 and 2 are consistent with the interpretation of climatic amelioration associated with paleogeographic changes in Gondwana occurring during the Pennsylvanian and Cisuralian.